A new B-Learning methodology for Teaching Differential integral calculus in a school of Engineering (LACCEI, 2024)
The great technological advances of the contemporary digital age have allowed us to take giant steps in the creation of new learning environments and educational methodologies. The research described in this article presents the application of a blended learning methodology in English abbreviated as B-learning (Blended learning) where face-to-face training guided by a teacher is combined without this being the center of the learning model and at the same time the educational model is complemented with elements of virtual education under the flipped classroom pedagogical approach , where the teaching-learning process focuses on the student, making him or her the protagonist and main actor. The teacher becomes a guide for the interaction of knowledge exchange between the participants and the counselor of the process. This methodology was applied as part of the return to face-to-face pilot in the Differential and Integral Calculation course at the School of Engineering of an Ecuadorian university in 2021, showing a higher approval rate and improvement in performance than the group of students who continued studying the subject in virtual modality with a traditional teaching methodology.